Genetic Diversity Assessment of Quantitative Traits in Landraces of Aus Rice - Siddique, M. A.; Khalequzzaman, M.; Islam, M. Z.; Baktiar, M. H. K.; Ahmed, M. S. (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Genetic diversity of 46 landraces of Aus rice was studiedunder irrigated condition through Mahalanobis D2 statistics for grain yield and yield contributing characters. The genotypes were grouped into seven clusters. The highest inter-genotype distance was observed between the genotypes Lalgalong and Langrabeni and the lowest between Saita and Korchamuri respectively. The intra cluster distances were low for all the clusters ranging from 0.64 in cluster IV to 1.17 in cluster I. The highest inter cluster value was 11.45 (between cluster III and V) and the lowest was 4.36 (between cluster VI and VII). The highest cluster means for effective tiller number and grain yield per hill were obtained from cluster III. On the other hand, the highest leaf width and the highest spikelet fertility from cluster IV, tallest plant and the highest grain breadth from cluster VI, the highest 1000-grain weight from cluster V whereas the lowest mean value for days to 50% flowering and days to maturity were found in cluster VI.The genotypes from cluster III could be hybridized with the genotypes of other clusters for producing transgressivesegregants. Canonicalvectoranalysis revealed that days to 50% flowering and days to maturity were contributed maximum to the genetic divergence. Principal Coordinate Analysis (PCoA) revealed that the genotypes Begun bitchi, Rang mahal, Laxmijhota, Katar, Chiknal, Manikmendal, Baismugurwere found far away from the centroid of the cluster and can be selected as parents for further breeding programs.The results suggested thatLalgalong (acc. no. 1655) and Langrabeni (acc. no. 1645) can be crossed with the genotypes of cluster III and cluster VI to develop more promising as well as high yielding variety for Aus season.